Pemanfaatan Big Data Analytics dalam Deteksi Fraud dan Prediksi Kinerja Keuangan: Kajian Literatur - Cindy Milasari Sitanggang; Meylin Simalango; Restina Purba; Jufri Darma (Politeknik Negeri Jakarta, 2025)
ABSTRAC The rapid advancement of digital technology has encouraged the adoption of Big Data Analytics (BDA) in various fields, including accounting and finance. This study aims to examine the utilization of BDA in fraud detection and financial performance prediction based on recent literature reviews. The research was conducted by analyzing academic articles and prior studies published since 2021. The findings indicate that BDA significantly contributes to detecting potential fraud by identifying complex data patterns that traditional methods often fail to capture. Moreover, BDA has proven effective in improving the accuracy of financial performance predictions by incorporating broader and real-time variables. This study concludes that BDA is a relevant and adaptive solution to address the challenges of fraud detection and financial forecasting in the big data era, while also providing opportunities for further research in accounting and information systems. Keywords : Big Data Analytics, fraud, financial performance